Kepemimpinan Kepala Sekolah dalam Pengelolaan Ekstrakurikuler di MI Nahdatul Ulama Sumber Agung - Syahri Syahri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Extracuricular is needed by the education unit as a forum to develop the interests and talents of learners. The purpose of this study is how the role of the principal's leadership in the sustainability of extracurricular management at MI Nahdatul Ulama Sumber Agung. The research methods used in this study are qualitative, data sources through interviews, observations, and documentation. The results of this study are 1) The process of managing the cocurricular by the principal at MI Nahdatul Ulama Sumber Agung is carried out from the formulation, formulation, utilization, to the stage of evaluation and control of activities. 2) The obstacles faced in the extracurricular management of MI Nahdatul Ulama Sumber Agung are the difficulty of getting competent supervisors according to the field, sometimes difficulty to get infrastructure, and also obstacles in motivating learners to continue to be excited to follow the activities. 3) The result of the principal's leadership in managing extracurriculars at MI Nahdatul Ulama Sumber Agung is the interest and talent of students can be included in the race.